2020
DOI: 10.1044/2019_jslhr-19-00204
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Acoustics and Speech Intelligibility in Young Adults With Down Syndrome

Abstract: Purpose Speech production deficits and reduced intelligibility are frequently noted in individuals with Down syndrome (DS) and are attributed to a combination of several factors. This study reports acoustic data on vowel production in young adults with DS and relates these findings to perceptual analysis of speech intelligibility. Method Participants were eight young adults with DS as well as eight age- and gender-matched typically developing (TD) contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The acoustic data supplements the perceptual data by providing objective support for the subjective impressions (Ansel and Kent 1992). This information can guide decision-making for the intervention process by providing insight regarding the nature of the disorder, notably whether the deficit is motor in nature (Carl et al 2020). Furthermore, targeting impaired vowel production within intervention may have a direct positive impact upon speech intelligibility (Lansford and Liss 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The acoustic data supplements the perceptual data by providing objective support for the subjective impressions (Ansel and Kent 1992). This information can guide decision-making for the intervention process by providing insight regarding the nature of the disorder, notably whether the deficit is motor in nature (Carl et al 2020). Furthermore, targeting impaired vowel production within intervention may have a direct positive impact upon speech intelligibility (Lansford and Liss 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Different measures of acoustic vowel space have been applied to dysarthric speech of various aetiologies, including children with developmental dysarthria (Hustad et al 2010), adolescents with Down syndrome (DS; Carl et al 2020), and adults with acquired dysarthria (Fletcher et al 2017), and have demonstrated correlations with speech intelligibility (e.g., in children and adolescents with CP; Higgins andHodge 2002, Liu et al 2005). A review of the literature reveals several common measures that have been applied to the measurement of vowel acoustics in typical and disordered speech.…”
Section: Vowel Acoustics In Developmental Dysarthriamentioning
confidence: 99%
See 3 more Smart Citations